The Validity of Module Based on Problem Based Learning (PBL) on Bacteria-Material for Grade X Senior High School - Fanny Felecia Audia; Indra Hartanto; Ganda Hijrah Selaras; Armen Armen (Universitas Negeri Padang, 2019)
On application Curriculum 2013 the learning more emphasize on approach scientific. One of model used by the teacher is PBL, but the implementation of the model has not been optimal in the learning process. The cause not yet optimal because there is no PBL-based teaching material available on Biology subjects. Based on the problems, the researchers have developed a PBL-based biological module bacterial material for Grade X senior high school students. However, the module that has been developed is unknown validity level. Therefore, the authors test the validity of the module developed. Assessment of module validity is carried out by validators who are experts in their respective fields of science, namely 2 lecturers majoring in Biology, Faculty of Math and Nature Science, State University of Padang and one of Biology teacher at SMAN 1 Lubuk Alung. Overall the average results of the PBL practice module based biological questionnaire on bacterial material for class X students of SMAN 1 Lubuk Alung were 3,49% with a very valid category. It shows that the modules that have been developed are very valid from the aspect of feasibility of content, language, presentation, graphics, and PBL on the evaluation of the validator.